Bacterial Blight Induced Shifts in Endophytic Microbiome of Rice Leaves and the Enrichment of Specific Bacterial Strains With Pathogen Antagonism - Yang, Fenghuan; Zhang, Jie; Zhang, Huaying; Ji, Guanghai; Zeng, Liexian; Li, Yan; Yu, Chao; Fernando, W. G. Dilantha; Chen, Wen (Frontiers in Plant Science, 2020)
The endophytic microbiome plays an important role in plant health and pathogenesis. However, little is known about its relationship with bacterial blight (BB) of rice caused by Xanthomonas oryzae pv. oryzae (Xoo). The current study compared the community compositional structure of the endophytic microbiota in healthy and BB symptomatic leaves of rice through a metabarcoding approach, which revealed BB-induced a decrease in the alpha-diversity of the fungal communities and an increase in the bacterial communities. BB-diseased rice leaves were enriched with saprophytic fungi that are capable of decomposing plant cell walls (e.g. Khuskia spp. and Leptosphaerulina spp), while healthy rice leaves were found to be significantly more abundant with plant pathogens or mycotoxin-producing fungi (e.g. Fusarium, Magnaporthe, and Aspergillus). The endophytic bacterial communities of BB-diseased leaves were significantly enriched with Pantoea, Pseudomonas, and Curtobacterium, strains. Pantoea sp. isolates from BB leaves are identified as promising candidates for the biocontrol of BB for their ability to inhibit in vitro growth of Xoo, suppress the development of rice BB disease, and possess multiple PGP characteristics. Our study revealed BB-induced complexed changes in the endophytic fungal and bacterial communities of rice leaves, and demonstrated that BB-associated enrichment of some endophytic bacterial taxa, e.g. Pantoea sp. isolates, may play important roles in suppressing the development of BB disease in rice.